Effect of ionising radiation on the characteristics of a MOSFET - Dasgupta S.; Chakrabarti P. (My University, 2025)
The effect of radiation-induced changes on the characteristics of an n-channel MOSFET has been investigated theoretically. A one-dimensional semi-numerical model of the device has been developed which can estimate fairly accurate characteristics of the device under unirradiated and irradiated conditions. The effect of ionising radiation on the channel voltage and electric field profile in the channel has been estimated numerically for the first time. The present model enables one to determine the ID-VD and transfer characteristics of the device by considering the field dependent mobility of the surface channel in the irradiated condition. The model presented here can be used as a basic tool for analysing MOS transistors exposed to a nuclear environment.